2007
DOI: 10.1038/sj.mp.4001969
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of gene expression in the limbic system of suicides with and without major depression

Abstract: The limbic system has consistently been associated with the control of emotions and with mood disorders. The goal of this study was to identify new molecular targets associated with suicide and with major depression using oligonucleotide microarrays in the limbic system (amygdala, hippocampus, anterior cingulate gryus (BA24) and posterior cingulate gyrus (BA29)). A total of 39 subjects were included in this study. They were all male subjects and comprised 26 suicides (depressed suicides = 18, non depressed sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
109
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(133 citation statements)
references
References 102 publications
21
109
2
1
Order By: Relevance
“…In addition to SAT1, other genes active during polyamine catabolism were also investigated. Gene expression levels of SAT2, an acetyltransferase that shares identity and homology with SAT1 [53], and ornithine aminotransferase-like 1, involved in the production of ornithine, were both found to be increased in the hippocampus of suicide completers [54]. In addition, the expression levels of spermine oxidase (SMOX) and spermine synthase (SMS), enzymes responsible, respectively, for the breakdown and synthesis of spermine, were altered in suicide completers.…”
Section: -Polyamine Gene Expressionmentioning
confidence: 99%
“…In addition to SAT1, other genes active during polyamine catabolism were also investigated. Gene expression levels of SAT2, an acetyltransferase that shares identity and homology with SAT1 [53], and ornithine aminotransferase-like 1, involved in the production of ornithine, were both found to be increased in the hippocampus of suicide completers [54]. In addition, the expression levels of spermine oxidase (SMOX) and spermine synthase (SMS), enzymes responsible, respectively, for the breakdown and synthesis of spermine, were altered in suicide completers.…”
Section: -Polyamine Gene Expressionmentioning
confidence: 99%
“…The first talk (Gustavo Turecki; McGill University, Canada) showed the utility of genome-wide expression studies, 13 here presenting a novel strategy for dealing with genetic heterogeneity by using an Extreme Value Analysis (EVA), examining genes in top 5% and with > 3-fold change in gene expression over 17 different brain regions in subgroups of suicides. Results showed reduction in mainly astrocytic gap junction genes GJA1 and GJB6, and transcription factor SOX9, among B20% of the suicides.…”
Section: Daymentioning
confidence: 99%
“…Numerous postmortem studies have shown abnormalities of histology, morphometry, neurochemistry and gene expression in the hippocampus of people with schizophrenia, 1-3 bipolar disorder [4][5][6] and depression. 5,[7][8][9] Individuals with schizo phrenia have shown hippocampal hypofunctionality with simultaneous prefrontal cortex hyperactivation during episodic memory retrieval tasks. 10,11 Moreover, functional neuroimaging reveals a connection between overactivation of the hippocampus and the positive psychotic symptoms of schizophrenia, such as hallucinations and delusions.…”
Section: Introductionmentioning
confidence: 99%